Design of Gate 4 at IPB University and the Babakan Raya-Dramaga Road intersection to improve traffic performance of the campus’s external area - Muhamad Adlijil Ikram; Sudibyo, Tri (Jurnal Teknik Sipil dan Lingkungan, 2025)
Population growth and increased mobility in the area surrounding IPB University, particularly along Raya Dramaga Road and the Babakan Raya intersection have led to severe congestion. This intersection serves as a critical point where vehicle accumulation frequently occurs due to crossing movements, particularly during morning and evening peak hours. The majority of vehicles involved in these crossings are motorcycles owned by IPB students heading toward the university’s main gate. Therefore, effective measures or policies are required to reduce crossing movements during peak hours, such as redirecting a portion of student traffic to alternative gates to alleviate congestion at Babakan Raya intersection. This study aims to identify traffic volume, road and intersection capacity, and the actual intersection performance, design an optimal Gate 4 for IPB, and analyze its impact on traffic performance. The research methodology includes primary and secondary data collection, intersection performance analysis, and the design of a roundabout and intersection improvements based on PKJI 2023 standards and Transportation Ministerial Regulation No. 96 of 2015. The study findings indicate that widening minor approach lanes, constructing traffic islands, and eliminating side friction increase the capacity of Babakan Raya intersection from 2,985.32 PCU/hour to 3,413.88 PCU/hour. The degree of saturation decreases from 1.22 to 0.87, and intersection delay is significantly reduced from 46 seconds/PCU to 14 seconds/PCU, improving the level of service (LoS) from category E (poor) to B (good). The construction of Gate 4 at IPB successfully redirects vehicle flow, particularly motorcycles, which previously traversed Babakan Raya intersection to access Gate 1 of IPB. With a capacity of 2,149 PCU/hour, the Gate 4 roundabout effectively accommodates high vehicle volumes during peak hours. Traffic performance analysis results demonstrate that intersection improvements and the development of Gate 4 at IPB effectively enhance traffic performance in the external area of IPB, mitigate congestion, and improve vehicular movement efficiency.